THE CONCEPT OF PROVIDING RULE-MAKING PROCESS WITH INFORMATION (TSUL LEGAL REPORT, 2026)
This article analyzes the concept, essence and charactristics of providing rule-making process with information. Along with encyclopedic materials of the Republic of Uzbekistan, the approaches and opinions of scientists have been discussed. As part of the study, the normative legal acts of the Repubic of Uzbekistan have been analyzed in detail. Author’s definitions for the relevant notions have been developed which means that the writer achieved the purpose of this scientific research. In fact, in addition to legal research, the author developed scientifically proved definitions of several legal terms such as “information”, “information used in the rule-making process” and “providing rule-making process with information”. The issue of developing requirements for information in national legislation will be discussed by studying the scientific views on the information applied in rule-making process and the concept of providing rule-making process with information. It also examines the relevance of all types of information, regardless of the form, type, and stage of rule-making process and the importance of normative legal acts in determining viability, sustainability, and regulatory impact. It is recognized that information supply in the rule-making process and the mechanism of regulation of certain social relations affects the rational and effective perception of the normative legal acts by the general public.